1976
DOI: 10.1001/archneur.1976.00500050037007
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Variability in Determination of Plasma Antiepileptic Drug Concentrations

Abstract: The usefulness of plasma antiepileptic drug concentrations in treatment of epilepsy has been established, and many laboratories provide this service. A "blind" survey utilizing pooled patient plasma samples was conducted among 197 laboratories in the United States and Canada to establish the interlaboratory reproducibility. Three "patient specimens" containing different amounts of phenobarbital, phenytoin (diphenylhydantoin), primidone, and ethosuximide were employed; 112 laboratories reported results within f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…By organizing distribution centres they were able to submit the specimens to the laboratories as if they had been taken from patients locally, and the samples were therefore not given special treatment. Their results deserve wide publicity because they highlight the appalling quality of drug estimations (Pippenger, Penry, White, Daly & Buddington, 1976). For each specimen the range of results reported was from zero to levels which were so high as to be compatible only with a massive fatal overdose, and the inter-laboratory coefficients of variation ranged from 38-505%.…”
Section: Drug Level Monitoring -Quantity and Qualitymentioning
confidence: 91%
“…By organizing distribution centres they were able to submit the specimens to the laboratories as if they had been taken from patients locally, and the samples were therefore not given special treatment. Their results deserve wide publicity because they highlight the appalling quality of drug estimations (Pippenger, Penry, White, Daly & Buddington, 1976). For each specimen the range of results reported was from zero to levels which were so high as to be compatible only with a massive fatal overdose, and the inter-laboratory coefficients of variation ranged from 38-505%.…”
Section: Drug Level Monitoring -Quantity and Qualitymentioning
confidence: 91%
“…McAllister and Tait1"2 stated that the 'usual' dose given to adults produces serum levels of 11-21 ,umol/l, and it has therefore been suggested that organisms with MICs <11 ,umol/l should be considered sensitive to tobramycin.113 According to a commercial report,"4 sustained levels above 26 ,umol/l are likely to produce adverse effects and should be avoided. Although the incidence of both nephro-and ototoxicity may be marginally less with tobramycin than with gentamicin,"5 and there is little documentary evidence of a relationship between toxicity and drug level, a therapeutic plasma range of [11][12][13][14][15][16][17][18][19][20][21] ,umol/l has been suggested and good results shown when such levels were achieved in the treatment of serious infections. "6 Although a relationship between trough level and toxicity has not been found, rising trough levels give warning of accumulation, and if these are kept below 2 ,tmol/1, the corresponding peak level is usually <21 [Imol/1.…”
Section: Salicylatementioning
confidence: 99%
“…It was also evident that the application of modern pharmacology to the use of currently marketed drugs would result in improved seizure control for some patients. The Epilepsy Branch has attempted t o improve the methodology for quantitative analysis of blood levels of antiepileptic drugs and to extend the accurate use of blood drug levels into therapeutic practice (Rose et al, 1971;Kupferberg, 1972;Kutt and Penry, 1974;Kupferberg and Penry, 1975;Pippenger et al, 1976;Pippenger et al, 1978). For many patients, however.…”
Section: Status Of Antiepileptic Drug Therapy In 1970mentioning
confidence: 99%